PROCESS-GENRE APPROACH: THE IMPLEMENTATION AT STKIP PGRI BLITAR IN TEACHING WRITING - NOVI SRIWULANDARI; RANI MUNTASARI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2018)
This study was intended to apply process-genre approach to solve the problems of the students of Class IIB of STKIP PGRI Blitar in the academic year of 2011/2012 in writing a descriptive paragraph. The research designed used in this study was collaborative Classroom Action Research. To get the data, the researcher used several instruments (e.g. observation sheet, and questionnaire). The finding showed that the students of Class IIB could write their descriptive paragraphs much better.